Hero-systems, military dictatorship, and the silencing of the academic community in Suriname - Natascha Adama (Nuovi autoritarismi e democrazie: diritto, istituzioni, società, 2021)
This paper is concerned with academic silencing in Suriname and its links with the conflict that took place at the national level, which was given scant consideration in research. Emphasis will be given to the establishment of the hero-system in order to ensure peace and the connections between academic silencing, dictatorship and law and order.